Nutrient addition bioassay and phytoplankton community structure monitored during autumn in Xiangxi Bay of Three Gorges Reservoir, China. (May 2020) - Nwankwegu, Amechi S.; Li, Yiping; Huang, Yanan; Wei, Jin; Norgbey, Eyram; Lai, Qiuying; Sarpong, Linda; Wang, Kai; Ji, Daobin; Yang, Zhengjian; Paerl, Hans W.
Abstract: The increasing freshwater ecosystem nutrient budget is a critical anthropogenic factor promoting freshwater eutrophication and episodic bloom of harmful algae which threaten water quality and public health. To understand how the eutrophic freshwater ecosystem responds in term of phytoplankton community structure dynamics to a sudden rise in nutrient concentrations, a microcosm study by nutrient addition bioassay was implemented in Xiangxi Bay (XXB) of Three Gorges Reservoir, China. Our results showed that dissolved trace elements supply adequately altered the phytoplankton community structure creating a regime shift from cyanobacteria-dominated to essentially Chlorophytes-dominated system, relative abundance (>70%). Combined N, P, and Si led to maximum growth stimulation accompanied by the highest chlorophyll yield (82.7 ± 14.01 μgL −1 ) and growth rate (1.098 ± 0.12 μgL −1 d −1 ). N separate additions resulted in growth responses which did not differ while P -addition differed significantly (p∠0.05) with the control justifying a P limited system. Si enrichment stimulated diatom growth, relative abundance (20.62%) and maximum utility rate (USi  = 83.37 ± 0.33%). This study also reveals that increasing nutrient loading from anthropogenic sources adequately decrease the ecological diversity (H < 1) and community overlap (CC ≤ 0.5) intensifying competition and succession which then select the fast-growing taxa to dominate and expand. Result points to the need for multiple nutrient control of N, P and Si loading into XXB through a prudent nutrient management protocol for lasting bloom mitigation in the tributary bay. Graphical abstract: Image 1 Highlights: Episodic HABs events are driving by increasing nutrient budget and constantly changing climate. Increasing nutrient paradigm greatly affects biological diversity and exacerbates competition and succession. Trace metal addition causes a community transition from Cyanobacteria to Chlorophyte dominated system. Combined N, P and Si addition stimulates growth rate and optimizes biomass production (as chla).